New view on the organization and evolution of Palaeognathae mitogenomes poses the question on the ancestral gene rearrangement in Aves - Urantówka, Adam Dawid (BMC Genomics, 2020)
BACKGROUND: Bird mitogenomes differ from other vertebrates in gene rearrangement. The most common avian gene order, identified first in Gallus gallus, is considered ancestral for all Aves. However, other rearrangements including a duplicated control region and neighboring genes have been reported in many representatives of avian orders. The repeated regions can be easily overlooked due to inappropriate DNA amplification or genome sequencing. This raises a question about the actual prevalence of mitogenomic duplications and the validity of the current view on the avian mitogenome evolution. In this context, Palaeognathae is especially interesting because is sister to all other living birds, i.e. Neognathae. So far, a unique duplicated region has been found in one palaeognath mitogenome, that of Eudromia elegans. RESULTS: Therefore, we applied an appropriate PCR strategy to look for omitted duplications in other palaeognaths. The analyses revealed the duplicated control regions with adjacent genes in Crypturellus, Rhea and Struthio as well as ND6 pseudogene in three moas. The copies are very similar and were subjected to concerted evolution. Mapping the presence and absence of duplication onto the Palaeognathae phylogeny indicates that the duplication was an ancestral state for this avian group. This feature was inherited by early diverged lineages and lost two times in others. Comparison of incongruent phylogenetic trees based on mitochondrial and nuclear sequences showed that two variants of mitogenomes could exist in the evolution of palaeognaths. Data collected for other avian mitogenomes revealed that the last common ancestor of all birds and early diverging lineages of Neoaves could also possess the mitogenomic duplication. CONCLUSIONS: The duplicated control regions with adjacent genes are more common in avian mitochondrial genomes than it was previously thought. These two regions could increase effectiveness of replication and transcription as well as the number of replicating mitogenomes per organelle. In consequence, energy production by mitochondria may be also more efficient. However, further physiological and molecular analyses are necessary to assess the potential selective advantages of the mitogenome duplications. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-020-07284-5.